Profit Kurikulum Merdeka Belajar di SMK Cendikia Batujajar - Dean Dylan; Muhamad Reihan; Rio Fazriono; Ripa Hikmah; Rizal Faqih (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Independent Learning Curriculum  is a curriculum implemented in Indonesia with the aim of strengthening students' basic competencies and enabling schools to have flexibility in determining learning programs. The application of   Independent Learning Curriculum in Vocational High Schools  has its own challenges because SMKs have a more specific goal, namely to equip students with skills and knowledge relevant to the world of work. This study aims to explore the application of  Independent Learning Curriculum in Vocational Schools and its impact on the quality of learning. This research uses a qualitative approach with a case study method. Data is collected through Google From to students at Vocational Schools who apply Independent Learning Curriculum. The results of the research show that the implementation of Independent Learning Curriculum in Vocational High Schools requires careful preparation, including a deep understanding of Independent Learning Curriculum and its implementation, as well as the selection and development of learning programs that are in accordance with the objectives of the Vocational Schools. Even though there are several challenges in implementing  Independent Learning Curriculum in Vocational Schools, such as lack of resources and limited time, Independent Learning Curriculum provides flexibility for teachers and schools in adapting learning programs to the needs of students and the world of work. The impact of implementing  Independent Learning Curriculum in Vocational Schools can be seen in improving the quality of learning and student satisfaction. Students feel more involved in learning and are better prepared to face the world of work after graduating from Vocational Schools. However, it is necessary to carry out continuous evaluation of the implementation of Independent Learning Curriculum in Vocational Schools in order to ensure that learning programs that are adapted to the needs of students and the world of work can continue to be improved.